Educational Accommodations for Students With Disabilities: Two Equity-Related Concerns - Lovett, Benjamin J. (Frontiers in Education, 2021)
Educational accommodations are frequently given to students with disabilities. For instance, students might be given a copy of class notes or provided additional time to complete a test. One purpose of accommodations is to improve educational equity, putting all students on equal footing. However, research on current accommodations practices raises two distinct equity-related concerns. First, students from privileged backgrounds are more likely to receive certain accommodations even without adequate evidence of need; this can provide an unfair boost in performance and widen gaps among students. Second, when students from less privileged backgrounds are given accommodations, the incentive for schools to provide academic remediation, compensatory strategies, and coping skills is lessened, leaving these students in a worse position when accommodations are not available outside of educational settings. Implications for practice are discussed.